2021
DOI: 10.1097/ogx.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stillbirth: An Umbrella Review of Evaluation of Prognostic Variables

Abstract: Background: Stillbirth accounts for over 2 million deaths a year worldwide, and rates remains stubbornly high. Multivariable prediction models may be key to individualised monitoring, intervention or early birth in pregnancy to prevent stillbirth.Objectives: To collate and evaluate systematic reviews of factors associated with stillbirth in order to identify variables relevant to prediction model development.Search strategy: Medline, Embase, DARE and Cochrane Library databases and reference lists were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…25 The study reported that no marker had useful screening performance, but maternal age, body mass index and history of previous adverse pregnancy outcomes had a more convincing association than the best performing tests, which were PAPP-A, placental growth factor and UtA-PI. 25 Such types of publications that do not recognise the fact that the causes of stillbirth are heterogeneous could not advance the development of strategies for prediction and prevention of stillbirth.…”
Section: Comparison With Results Of Previous Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…25 The study reported that no marker had useful screening performance, but maternal age, body mass index and history of previous adverse pregnancy outcomes had a more convincing association than the best performing tests, which were PAPP-A, placental growth factor and UtA-PI. 25 Such types of publications that do not recognise the fact that the causes of stillbirth are heterogeneous could not advance the development of strategies for prediction and prevention of stillbirth.…”
Section: Comparison With Results Of Previous Studiesmentioning
confidence: 98%
“…In a series of previous first‐ and second‐trimester studies for the prediction of stillbirth we highlighted that the causes of this adverse event are heterogeneous and that the focus of research should be placental dysfunction related stillbirths because they are relatively common and, to a great extent, potentially preventable 19–24 . However, a systematic review of 69 previous systematic reviews that aimed to identify variables that could be relevant to the development of a clinical prediction model for stillbirth treated this adverse event as a homogeneous condition 25 . The study reported that no marker had useful screening performance, but maternal age, body mass index and history of previous adverse pregnancy outcomes had a more convincing association than the best performing tests, which were PAPP‐A, placental growth factor and UtA‐PI 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews using aggregate data meta-analysis currently represent the best available evidence on predictors of stillbirth and have proposed several risk factors to categorize women as high risk 41 . However, they are limited by heterogeneity among the primary studies, such as in the definition of stillbirth 41 .…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Systematic reviews using aggregate data meta-analysis currently represent the best available evidence on predictors of stillbirth and have proposed several risk factors to categorize women as high risk 41 . However, they are limited by heterogeneity among the primary studies, such as in the definition of stillbirth 41 . Existing primary studies are often small, with imprecise estimates and are inconsistent in the confounding factors adjusted for in 28 (St George's dataset 42 ).…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…27 Another limitation may be failure to control for other maternal co-morbidities known to be associated with stillbirth, such as sickle-cell disease or antiphospholipid syndrome, in the general population. 34 Although we observed a temporal reduction of nicotine consumption in the general population, which is known to be a very important measure in reducing stillbirth, 35 we acknowledge that smoking history TA B L E 2 Sample characteristics of the stillbirth cohort (N = 2579) in non-anomalous pregnancies ≥24 +0 gestational weeks before ("pre-GDM screening," i.e., January 2008 to December 2010) and after ("GDM screening," i.e., January 2011 to December 2019) implementation of the universal gestational diabetes screening program in Austria b Missing values N = 959. BMI categories: underweight (≤18.5 kg/m 2 ), normal (18.6-24.9 kg/m 2 ), pre-obesity (25.0-29.9 kg/m 2 ), obesity (≥30.0 kg/m 2 ).…”
Section: One Example Of Such Data Is the Midlands And North Of Englandmentioning
confidence: 99%